Choice without Awareness: Ethical and Policy Implications of Defaults. (September 2013) - Smith, N. Craig; Goldstein, Daniel G.; Johnson, Eric J.
Defaults have such powerful and pervasive effects on consumer behavior that they could be considered "hidden persuaders" in some settings. Ignoring defaults is not a sound option for marketers or consumer policy makers. The authors identify three theoretical causes of default effects—implied endorsement, cognitive biases, and effort—to guide thought on the appropriate marketer and policy maker responses to the issues posed for consumer welfare and consumer autonomy, including proposals for benign "nudges" of behavior. Defaults can be a preferred form of decision architecture; that is, other nonconscious influences on choice and an absence of established preferences can mean that active choice is not always the better alternative. The authors propose "smart defaults" as welfare-enhancing and market-oriented alternatives to the current practice of generally ignoring default effects. Their analysis highlights the importance of considering the process as well as the outcomes of consumer decision making and taking responsibility for consumers' mistakes arising from misuse of defaults. The authors conclude by reflecting on the ethical and policy implications of techniques that influence consumer choice without awareness.